135P Analysis of the immune microenvironment in pre-treatment non-small cell lung cancer (NSCLC) patients with follow-up response data to second-line immunotherapy. (15th December 2019) - Bhagat, M; Warren, S; Elliott, N; Womack, C; Memeo, L; Colarossi, L; Cumberbatch, M
Abstract: Background: Patients selected based on PD-L1 expression for second-line immune checkpoint inhibitor (ICI) treatment are often identified using archival specimens collected months or years prior to starting immunotherapy. Such patients may have received and failed multiple lines of standard of care (SOC) treatments with subsequent potential impact on PD-L1 expression and immune microenvironment. Methods: We have analysed formalin fixed paraffin embedded (FFPE) tissues in a cohort of NSCLC patients (n = 16) taken during resection performed as first-line surgical treatment for which radiotherapy, SOC chemotherapy, and second-line immunotherapy clinical follow-up data are available. The immune microenvironment was evaluated by immunohistochemistry (IHC) plus digital image analysis for CD3, CD8, PD-L1, CD68 and CD163, and by Nanostring using the IO360 TM gene expression panel, with the aim of exploring whether immune signatures predictive of response to ICI therapy may be identified in such samples. Results: Clinical follow-up data indicated objective response to ICI therapy for 4/16 patients (n = 2 Nivolumab, n = 1 Pembrolizumab, n = 1 Durvalumab) with time from first diagnosis to receiving second-line ICI treatment ranging from 5 to 102 (mean 33.6) months. During this time these patients received various lines of radiotherapy and SOC chemotherapy prior to receiving immunotherapy. While the Tumor Inflammation Signature was not predictive of response, gene expression analysis did identify several signatures associated significantly with response, including increased abundance of CD8 T cells, cytotoxic cells, cytotoxicity, MHC class II antigen presentation and Melanoma-Associated Antigens (MAGE). These data were supported by a significant elevation of CD8 T cells by IHC in the responder versus non-responder populations, from a mean of 329 to 961 CD8+ T cells/mm 2 . Conclusion: Taken together these data demonstrate that despite various lines of previous radiotherapy and chemotherapy spanning several years, immune profiles associated with response to second-line immunotherapy can be detected in surgical first-line resection samples. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: M. Bhagat: Shareholder / Stockholder / Stock options, Officer / Board of Directors: TriStar Technolgoy Group. All other authors have declared no conflicts of interest.